2016
DOI: 10.1097/dss.0000000000000582
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 532 nm Potassium Titanyl Phosphate Laser and 595 nm Pulsed Dye Laser in the Treatment of Erythematous Surgical Scars

Abstract: The-532 nm KTP laser is comparable in efficacy and safety to the 595-nm PDL laser in the treatment of erythematous surgical scars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 17 publications
1
33
0
Order By: Relevance
“…[50][51][52] With a substantive range of power densities, from <1 to 90 J/cm 2 for the 532 nm effect on scar (and presumably TGF-b), it is apparent that additional studies are required to optimize these effects in the setting of renal fibrosis. It is likely that more than one wavelength type at potentially more than one power density will be required to enhance epithelial and endothelial proliferation while reducing fibrotic activity and apoptosis.…”
Section: Discussionmentioning
confidence: 98%
“…[50][51][52] With a substantive range of power densities, from <1 to 90 J/cm 2 for the 532 nm effect on scar (and presumably TGF-b), it is apparent that additional studies are required to optimize these effects in the setting of renal fibrosis. It is likely that more than one wavelength type at potentially more than one power density will be required to enhance epithelial and endothelial proliferation while reducing fibrotic activity and apoptosis.…”
Section: Discussionmentioning
confidence: 98%
“…For example, in physical therapy, the use of PBMT is applied in postoperative phases as an aid in the muscular, nervous, joint, and other functional recovery processes, and in dentistry it is applied in the processes of dental extraction, grafting, osteonecrosis, and periodontal lesions [11,12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…PDL is effective in improving the vascularity, pliability, color, and height of hypertrophic scars and keloids. Previous studies have reported a 57% to 83% improvement in clinical appearance and texture of hypertrophic scars after one to two PDL treatments [299,300]. Non-ablative fractional lasers (NAFL) have been shown to significantly improve the pigmentation and thickness of surgical scars, atrophic scars, hypertrophic scars, and hypopigmented scars.…”
Section: Laser Therapymentioning
confidence: 99%